Penggunaan Model UML Dalam Sistem Informasi Pemesanan Pupuk Berbasis Web (Studi Kasus Pada UD. Bangun Tani Rantauprapat) - Putri Jesica Viktoria (Jurnal Informatika, 2022)
The application of information technology in a business field in this globalization era will have an impact on the results of company performance, because in this globalization era the information produced must be fast, accurate, valid and efficient which is needed by all relevant parts both internal and external to the company which is related. UD.Bangun Tani is a trading company which is engaged in selling various types of fertilizers and pesticides needed in the agricultural sector including plant fertilizers, pesticides, herbicides, vegetable and fruit seeds. UD.Bangun Tani aims to build an information system. Ordering the type of fertilizer based on Web using Localhost and design using the Unifed Lodeling Language (UML) with the existence of this system ordering this fertilizer will be increasingly resolved and managed in a computerized way.